THE PERFORMANCE AND THE INFLUENCE OF PHYSICAL INFRASTRUCTURES ON THE PLANT PRODUCTIVITY: A CASE STUDY APPROACH - Muhamad Hendrie Soesanto; Slamet Imam Wahyudi; M. Faiqun Niam (Jurnal Teknik Sipil dan Arsitektur, 2023)
Irrigation System Performance Index (ISPI) is often used as a parameter in making decisions about the use of irrigation canals. The increase in rice production is dependent on a good condition of physical infrastructures, including the main building, the carrier canal and the buildings on the carrier canal. Performance assessment of Physical Infrastructure and Plant Productivity in Sungapan irrigation area of Pemalang Regency indicated that the physical infrastructure performance in 2012 - 2022 was 38.42%, increasing 3.22%. While the performance assessment of Plant Productivity was 14.96%, increasing 2.99%. Based on the multiple regression analysis using simultaneous test (F), the Physical Infrastructure component was indicated to influence the plant productivity. Meanwhile, based on the partial test (t), the physical infrastructure component partially did not have a significant influence on the plant productivity